Cigarette smoke exposure impairs reverse cholesterol transport which can be minimized by treatment of hydrogen-saturated saline. Issue 1 (December 2015) - Zong, Chuanlong; Song, Guohua; Yao, Shutong; Guo, Shoudong; Yu, Yang; Yang, Nana; Guo, Zheng; Qin, Shucun
Abstract Background Cigarette smoke (CS) exposure impaired plasma lipid profiles by modification of apolipoproteins. Hydrogen (H2 ) has been proved effective on reducing oxidative stress or improving HDL functionalities in animal models or metabolic syndrome volunteers. This study was undertaken to explore the effects of CS exposure on reverse cholesterol transport (RCT) and the antioxidative effects of H2 treatment against CS exposure in mice transgenic for human cholesteryl ester transfer protein (CETP). Methods [3 H]-cholesterol-laden macrophages were injected intraperitoneally into mice, and the samples of blood, bile, liver, and feces were collected for radioactivity determination to evaluate RCT. [3 H]-cholesterol-laden macrophages were incubated with HDL isolated from different groups of mice, and the samples of cell medium supernatants were collected for evaluating the HDL functionality to elicit cholesterol efflux. Results CS exposure significantly decreased plasma HDL cholesterol level (HDL-C) by 22 % and increased LDL cholesterol level (LDL-C) by 21 % compared with the control group (p < 0.05, p < 0.01), while H2 treatment significantly improved the CS-impaired levels of TC, LDL-C and HDL-C by 10, 27 and 31 %, respectively, compared with the CS group (p < 0.05, p < 0.01 andp < 0.05). Besides, CS exposure significantly decreased [3 H] tracer concentrations in liver, bile and feces by 17, 35 and 48 %, respectively, compared with the control group (p < 0.05 for liver and feces), while H2 treatment significantly improved them by 21, 72 % and 89 %, respectively, compared with the CS group (allp < 0.05). Furthermore, CS exposure significantly decreased the HDL functionality to elicit cholesterol efflux by 26 % (p < 0.05), while H2 treatment also improved it by 32 % (p < 0.05). We did not find any significant alterations in protein expressions of RCT involved genes. Conclusions These findings provided direct evidence supporting the notion that CS exposure in vivo impairs plasma lipid profiles, HDL functionalities and macrophage-to-feces RCT pathway in CETP transgenic mice, all of which can be minimized by treatment of H2 -saturated saline.